2010
DOI: 10.1021/cm1011229
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and Microwave-Assisted Solvothermal Synthesis and Surface Modification of Co7 Brucite Disk Clusters and Their Magnetic Properties

Abstract: We present the comparative preparation of [Co 7 ( μ 3 -OH) 6 (L) 6 ](ClO 4 ) 2 3 12H 2 O (1), [Co 7 ( μ 3 -CH 3 O) 6 -(L) 6 ](ClO 4 ) 2 (2), and [Co 7 ( μ 3 -N 3 ) 6 (L) 6 ](ClO 4 ) 2 (3), where HL is 2-methoxy-6-[(methylimino)methyl]phenol, using traditional (e.g., 120 °C, 120 h, 23% yield for 1) and microwave-assisted (e.g., 120 °C, 10 min, 46% yield for 1) solvothermal synthesis. The structures contain Co 7 brucite disk [Co 7 ( μ 3 -X) 6 ( μ 2 -O) 6 ] 2þ , where the ligands are arranged in two open hemisphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 36 publications
2
56
0
Order By: Relevance
“…[Cd(3-NO 2 -bdc)(bbi)] n (1) and [Co (3-NO 2 -bdc)(bbi)] n (2) (3-NO 2 -bdcH 2 = 3-nitro-1,2-benzenedicarboxylic acid, bbi = 1,1′-(1,4-butanediyl)bis (imidazole)) are isostructural, which exhibit two-dimensional (2D) layer frameworks; [Co(3,5-pdc)(bbi) 2H 2 O] n (3) (3,5-pdcH 2 = pyridine-3,5-dicarboxylic acid) has 2D 6-connected network with a Schäfli symbol of (3 4 4 6 5 3 ). In addition, compounds 1 and 2 exhibit good photocatalytic activities under visible irradiation, and their different photocatalytic activities have also been analyzed based on the diffuse-reflectance UV/Vis spectra.Metal-organic frameworks (MOFs) are a relatively new class of crystalline coordination polymers, which have potential in a myriad of applications, including gas storage, chemical separation, heterogeneous catalysis and optical, electronic, magnetic materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Nowadays, much effort has also been devoted to developing new photocatalytic materials based on metal-organic frameworks, which is motivated largely by a demand for solving pollution problems in view of their potential applications in the green degradation of organic pollutants [16][17][18][19][20][21][22][23].…”
mentioning
confidence: 99%
“…[Cd(3-NO 2 -bdc)(bbi)] n (1) and [Co (3-NO 2 -bdc)(bbi)] n (2) (3-NO 2 -bdcH 2 = 3-nitro-1,2-benzenedicarboxylic acid, bbi = 1,1′-(1,4-butanediyl)bis (imidazole)) are isostructural, which exhibit two-dimensional (2D) layer frameworks; [Co(3,5-pdc)(bbi) 2H 2 O] n (3) (3,5-pdcH 2 = pyridine-3,5-dicarboxylic acid) has 2D 6-connected network with a Schäfli symbol of (3 4 4 6 5 3 ). In addition, compounds 1 and 2 exhibit good photocatalytic activities under visible irradiation, and their different photocatalytic activities have also been analyzed based on the diffuse-reflectance UV/Vis spectra.Metal-organic frameworks (MOFs) are a relatively new class of crystalline coordination polymers, which have potential in a myriad of applications, including gas storage, chemical separation, heterogeneous catalysis and optical, electronic, magnetic materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Nowadays, much effort has also been devoted to developing new photocatalytic materials based on metal-organic frameworks, which is motivated largely by a demand for solving pollution problems in view of their potential applications in the green degradation of organic pollutants [16][17][18][19][20][21][22][23].…”
mentioning
confidence: 99%
“…Enlightened (25), are reported by Gao and Bu by using a long ditopic spacer as a magnetic separator [62,63]. Compared with the previous Co(bt)(N 3 ) 2 SCM, the connection between the Co 2+ ions is similar; however, the chain structure is quite different in 24 and 25.…”
Section: (Iii) Single-molecule Magnets Composed Of Only 4f Ionsmentioning
confidence: 97%
“…However, micro-SQUID measurements on the single crystal of 1 revealed a thin hysteresis and suggested that it is not a real SMM. The main reasons are likely to be the significant spin-orbit interaction and the rhombic zero-field splitting parameter E [24][25][26].…”
Section: Representative Molecular Nanomagnets (A) the Development Of mentioning
confidence: 99%
“…Complex 4 has, as have a number of heptanuclear cobalt clusters, previously been synthesized as a potential single-molecular magnet, [111,112]. Cluster 4 is distinguished from other known clusters by the μ 3 -OH bridging units surrounding the central cobalt atom.…”
Section: Molecular Cobalt Complexes As Models For Co-oecmentioning
confidence: 99%